The Contribution of India's Private Sector to Defence Manufacturing - Das, Bharti; Colonel, Sanjay Sood (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
There has been a radical shift in the structure of the defence manufacturing ecosystem in India in the last twenty years with the slow removal of the state monopoly and the decisive involvement of the business industry as a key player. This essay discusses how the role of the Indian private sector in defence production has been changing, and how the role of this sector can be placed in the context of an overall trend of economic liberalisation, strategic autonomy and national security needs. It follows the historical path of the post-independence model where post-independence public sector dominated (1947-2000), the period of liberalisation beginning in 2001, the period of post-2014 which is the era of Make in India which has transformed the mode of governance of the defence industry. In this paper, the analysis of policy reforms is carried out including progressive FDI liberalisation, the Defence Acquisition Procedure (DAP) 2020, the Strategic Partnership Model, Positive Indigenisation Lists, and innovation-driven initiatives, iDEX, and Technology Development Fund. The paper draws on recent production and export statistics to point out the increment in the relative quantitative and qualitative contribution of the private enterprises that currently occupy more than 22 per cent of the domestic defence production and about 60-65 per cent of the defence exports. It also evaluates the rise of large privately controlled conglomerates and specialisation companies as system integrators, exporters, and technology developers with the help of defence industrial belts in Uttar Pradesh and Tamil Nadu. In addition to economic indicators, the paper highlights the strategic value of the involvement of the private sector, such as import substitution, supply-chain resiliency, technology absorption, and increased export competitiveness. Meanwhile, it points out in a critical manner the enduring challenges that were associated with the intensity of R&D, access to advanced technology, complexity in procurement and capital constraints. The paper concludes that the private sector has ceased being a peripheral player to being a structurally indispensable pillar of the Indian defence industrial base with far reaching repercussions on national security, strategic independence and India ambitions to become a global defence manufacturing powerhouse by 2029.